Cytotoxic activity of the genus Ferula (Apiaceae) and its bioactive constituents - Mehrdad Iranshahi; Ramin Rezaee; Mona Najaf Najafi; Ali Haghbin; Jamal Kasaian (Avicenna Journal of Phytomedicine, 2018)
Objective: The genus Ferula L. includes perennial flowering plants belonging to the Apiaceae family. This genus is a rich source of biologically active phytochemicals such as sulfur-containing derivatives, coumarins, sesquiterpenes, sesquiterpene lactones, sesquiterpene coumarins, glucuronic acid, galactose, arabinose, rhamnose, and daucane esters. Over the last decade, considerable attention has been paid to biological activities of these compounds; it is assumed that the most prominent biological features of the genus Ferula are their cytotoxic effects. This article discusses cytotoxic activity of the genus Ferula and their important compounds. Methods: In this mini-review article, papers published from 1990 to April 2016 were included and the following information was discussed; cytotoxic activity of the genus Ferula and their important compounds, the type of cell line used in vitro, concentrations of the extracts/active compound that were used, and the underlying mechanisms of action through which Ferula-related chemicals induced cytotoxicity. In addition, we explained different mechanisms of action through which the active constituents isolated from Ferula, could decrease cellular growth. Conclusion: It is highly recommended that potent and effective compounds that were isolated from Ferula plants and found to be appropriate as adjuvant therapy for certain diseases, should be identified. Also, the versatile biological activities of sesquiterpene coumarins suggest them as promising agents with a broad range of biological applications to be used in the future.